2018
DOI: 10.1128/aac.02462-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Daptomycin in Critically Ill Pediatric Patients

Abstract: The pharmacokinetics of daptomycin (10 mg/kg once daily) was studied in 4 critically ill pediatric patients aged 8 to 14 yrs. The area under the concentration-time curve from time zero to infinity (AUC) of plasma concentrations on day 1 ranged between 123.8 to 663.9 μg · h/ml, with lower values observed in septic and burn patients; clearance ranged from 15.1 to 80.7 ml/h/kg. Higher-than-recommended doses of daptomycin may be needed in septic children to ensure optimal drug exposure. Interpatient variability ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…2 case-reports and 1 pharmacometric model were available for daptomycin that included PK parameters [67][68][69]. Both patients in the case reports suffered from cardiac problems, a 13 year old boy with endocarditis [67] and a 8 year old girl with multi-organ failure (including renal insufficiency) awaiting heart transplantation [68].…”
Section: Daptomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…2 case-reports and 1 pharmacometric model were available for daptomycin that included PK parameters [67][68][69]. Both patients in the case reports suffered from cardiac problems, a 13 year old boy with endocarditis [67] and a 8 year old girl with multi-organ failure (including renal insufficiency) awaiting heart transplantation [68].…”
Section: Daptomycinmentioning
confidence: 99%
“…t½ in steady state was 4.58 h, with an AUC of 594 mg/l/h. The pharmacometric model by Antachopoulos included data of 4 patients aged from 8 to 14 years old with mixed disease conditions in their one compartment model [69]. On the first day of treatment, 3 of the 4 patients met pediatric criteria for sepsis.…”
Section: Daptomycinmentioning
confidence: 99%
“…Finally, we also found a few PK studies describing linezolid [102], ciprofloxacin [103], and daptomycin [104][105][106] PK in critically ill children (Table 3). [104] CL in sepsis patients is double the CL in non-critically ill children [104] Children with sepsis showed suboptimal AUC values, even with increased dosing. This was even more pronounced in the burn patient.…”
Section: Critical Illness Related Pharmacokinetic Alterations In Children and Infantsmentioning
confidence: 84%
“…Daptomycin could also be used in the treatment of children with MRSA infection [ 24 ], but little is known regarding its pharmacokinetics in critically ill children. Although a research [ 25 ] demonstrated comparable drug levels in pediatric septic patients compared with healthy volunteers and patients with milder infections, the study was based on a small number of patients and the results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%